Two Novel Pathogenic Variants of TJP2 Gene and the Underlying Molecular Mechanisms in Progressive Familial Intrahepatic Cholestasis Type 4 Patients - Tang, Jia; Tan, Meihua; Deng, Yihui; Tang, Hui; Shi, Haihong; Li, Mingzhen; Ma, Wei; Li, Jia; Dai, Hongzheng; Li, Jianli; Zhou, Shengmei; Li, Xu; et al. (Frontiers in Cell and Developmental Biology, 2021)
Progressive familial intrahepatic cholestasis (PFIC) is an autosomal recessive inherited disease which accounts for 10%~15% childhood cholestasis and could lead to infant disability or death. Mutations in the tight junction protein 2 gene (TJP2) were newly reported as pathogenic cause for PFIC type 4. We designed a multiplex polymerase chain reaction-based next generation sequencing method to detect TJP2 gene mutations in 267 PFIC patients and identified 3 known pathogenic mutations and 2 novel mutations in 3 patients. By using CRISPR-cas9 technology, we demonstrated TJP2 c.1202A>G was pathogenic at least partially by increasing the expression and nuclear localization of TJP2 protein. With minigene assay, we showed the TJP2 c.2668-11A>G was a new pathogenic mutation by inducing abnormal splicing of TJP2 gene and translation of prematurely truncated TJP2 protein. Furthermore, knock-down of TJP2 protein by siRNA technology led to inhibition of cell proliferation, induction of apoptosis, dispersed F-actin, disordered microfilaments and disappeared polarity in LO2 and HepG2celles. Global gene expression profiling of TJP2 knock-down LO2 cells and control LO2 cells identified 3169 down-regulated and 2812 up-regulated genes. Microtubule cytoskeleton genes were significantly down-regulated in TJP2 knockdown cells. The results of this study demonstrate that TJP2 c.1202A>G and TJP2 c.2668-11A>G are two novel pathogenic mutations and the cytoskeleton related functions and pathways might be potential molecular pathogenesis for PFIC.